A Survey of Cassini Images of Spokes in Saturn’s Rings: Unusual Spoke Types and Seasonal Trends - S. R. Callos; M. M. Hedman; D. P. Hamilton (The Planetary Science Journal)
Spokes are localized clouds of fine particles that appear over the outer part of Saturn's B ring. Over the course of the Cassini mission, the Imaging Science Subsystem obtained over 20,000 images of the outer B ring, providing the most comprehensive data set for quantifying spoke properties currently available. Consistent with prior work, we find that spokes typically appear as dark features when the lit side of the rings is viewed at low phase angles and as bright features when the rings are viewed at high phase angles or the dark side of the rings is observed. However, we also find examples of spokes on the dark side of the rings that transition between being brighter and darker than the background ring as they move around the planet. Most interestingly, we also identify spokes that appear to be darker than the background ring near their center and brighter than the background ring near their edges. These “mixed spokes” indicate that the particle size distribution can vary spatially within a spoke. In addition, we document seasonal variations in the overall spoke activity over the course of the Cassini mission using statistics derived from lit-side imaging sequences. These statistics demonstrate that while spokes can be detected over a wide range of solar elevation angles, spoke activity increases dramatically when the Sun is within 10° of the ring plane.